Poetics of underground space - Boschi, Antonello 1964- (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2022)
"The exploitation of land, especially in areas of particular value, has given rise to the need to reformulate the usual approach to building. If the development of urban sprawl, its infrastructure and its networks, generate increasingly compromised landscapes, what are the possible strategies to transform, expand and change the usual relationship between abuse of soil and unused subsoil? The book investigates the relationship architecture has with the underground. It provides a broad ranging historical and theoretical survey of, and critical reflection on, ideas pertaining to the creation and occupation of underground space. It overturns the classic dictates of construction on the surface and through numerous examples explores recoveries of existing voids, excavations, caves, quarries, grottos and burrows. Psychological, philosophical, literary and cinematographic legacies of underground architecture are mixed with the compositional, typological and constructive expedients, to produce a rich, diverse and compelling argument for these spaces"--Provided by publisher.
Huddling -- Notes from the underground -- The city other -- Mimicry -- Novelty is but oblivion -- Stone skies -- Sensations -- Sous passages -- Buried high-rises -- Brightening the dark.
Includes bibliographical references and index.
Keywords: Underground architecture; Underground areas